MANIFESTATIONS OF NEGATIVE MENTAL STATES IN ADOLESCENCE: CAUSES, CHARACTERISTICS, AND WAYS OF OVERCOMING THEM (Psychology Travelogs, 2025)
This article explores the manifestations of negative mental states in adolescence, their causes, characteristics, and potential ways to overcome them. The study examines the main factors influencing the mental health of young people, including social pressure, conflicts, academic stress, and changes in emotional and psychological states. Particular attention is given to the specific manifestations of anxiety, depression, aggression, and apathy during adolescence. The article outlines methods of psychological support, including the development of emotional resilience, psychocorrectional programs, and the importance of a healthy lifestyle. Additionally, the influence of modern technologies and social media on the mental health of young people is discussed. The article emphasizes the importance of creating a supportive social environment both in educational institutions and in families for maintaining the mental health of youth. It also highlights the need for systematic psychological support through individual counseling and group training. Furthermore, the article investigates the potential of modern psychotherapeutic methods such as art therapy and cognitive-behavioral therapy. Conclusions are drawn about the necessity of further research aimed at developing comprehensive programs to support adolescent mental health. These findings stress the importance of multi-level approaches that involve not only psychological interventions but also social and environmental factors that influence the mental well-being of adolescents. The article also explores the role of family and educational institutions in shaping adolescents' mental health, emphasizing the need for a proactive approach to mental well-being. It suggests that early identification of mental health issues can lead to more effective interventions and prevent the escalation of psychological problems.
Keywords: adolescence; mental states; anxiety; depression; psychocorrection; emotional resilience; social pressure